Pengaruh Modal Usaha, Lama Usaha Dan Jam Kerja Terhadap Pendapatan Usaha Pada Pelaku Ekonomi Kreatif Di Masa Pandemi Covid-19 (Sub Sektor Fashion-Kuliner Malang Raya) - Denia Alifiana; Jeni Susyanti; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine the prediction of business income for creative economy actors during the COVID-19 pandemic through business capital, length of business, and working hours. The sampling technique used was purposive sampling. The data sample obtained was 40 respondents from the population of creative economy actors in the fashion-culinary sub-sector of Malang Raya. Methods of data collection using the questionnaire method. The data analysis technique used in this research is multiple linear regression. The results of this study indicate that the variable of business capital can predict positively and significantly to operating income. Length of business can predict positively and significantly to operating income. Working hours can predict positively and significantly to operating income. Together, the variables of working capital, length of business, and working hours can predict positively and significantly the operating income.Keywords: business capital, length of business, working hours, operating revenues